Basic Financial Statement Analysis/Financial Statement Analysis/Analysis of Financial Statements (Book). - Winter, Sidney G.; Fisher, Allan J. (The Accounting Review, 1943)
Reviews several books. "Basic Financial Statement Analysis," by Alexander Wall; "Financial Statement Analysis," by John N. Myer and "Analysis of Financial Statements," by Harry G. Guthmann.